Protecting The Poor: using mobile technology to drive microinsurance adoption in Nigeria - Olugbenro, Samuel (Graduate School of Business (GSB), 2023)
Poor households throughout the world face twin disadvantages. The first is difficulty generating regular income, while the second is vulnerability to economic, political, and physical downturns. Harder still, the two problems reinforce each other: poverty is a vulnerability source, and repeated exposure to downturns reinforces poverty. Microinsurance has been used in other countries to reduce exposure to these vulnerabilities. However, the adoption of microinsurance is at its lowest; Nigeria's insurance industry contribution as a proportion of GDP is small. Given the success rate of microinsurance in many Asian countries, it is believed that microinsurance can help the country change the tide of poverty. Hence, the purpose of this research is to identify factors that determine the adoption of microinsurance among low-income earners in Nigeria, especially with the use of mobile technology. The study used a structured questionnaire to collect data from respondents in three villages in the Karu Local Government Area of Nasarawa State, Nigeria. Out of the 500 questionnaires, only 434 were usable. The data were analysed using multiple regression, and items on the questionnaire were tested for validity and reliability using principal component analysis and other validity convergence measures. The results from the analysed data show that trust, and perceived ease of use, of mobile technology, were highly significant in respondents' intentions to engage with microinsurance. In addition, although not as significant, family influence remained a driver of the adoption of microinsurance. Contrary to earlier beliefs, religion was not significant in the factors that influence microinsurance adoption. Therefore, policymakers and players in the insurance industry must build trust and create a new image for the sector in the country. Similarly, increased sensitisation on how microinsurance works is essential in bridging the knowledge gap about the microinsurance sector